Botanical Gardens, Trinidad, B.W.I. - (:unkn) unknown (My University, 2009)
A view of the well kept Botanical Gardens with its variety of tropical trees and plants and in the centre of the postcard a tall coniferous tree stands towering over all. Affixed to the back of the postcard is a 1 1/2 penny stamp.
Colour; Black and White; Style: Landscape; Other: Bordered, Undivided
Keywords: Trinidad and Tobago; Postcards; Botanical gardens--Trinidad and Tobago; Trees--Trinidad and Tobago; Plants--Trinidad and Tobago; 1920